2019
DOI: 10.3329/aajfss.v3i1.55921
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of nutritional quality of different fish feed available in greater Noakhali region, Bangladesh

Abstract: An experiment was carried out to comparative analysis of nutritional quality of different fish feed from different feed dealers and industries in greater Noakhali region and to compare the values with those provided by the manufacturers. The feed samples were collected from different feed industries and dealer's shop of these region. Feed samples were collected during 10 August to 5 September, 2016. The collected feed samples were stored and analyzed in the Fish Nutrition Laboratory of the Department of Aquacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Proximate composition such as moisture, crude protein, crude lipids, ash and nitrogen free extract (NFE) of poultry waste, and fly larvae were analyzed according to standard procedures given by AOAC (2005), Bhuiyan et al (2018), Nayeem et al (2019) and Khatun et al (2018).…”
Section: Determination Of Proximate Composition Of Poultry Waste and ...mentioning
confidence: 99%
“…Proximate composition such as moisture, crude protein, crude lipids, ash and nitrogen free extract (NFE) of poultry waste, and fly larvae were analyzed according to standard procedures given by AOAC (2005), Bhuiyan et al (2018), Nayeem et al (2019) and Khatun et al (2018).…”
Section: Determination Of Proximate Composition Of Poultry Waste and ...mentioning
confidence: 99%
“…On the other hand, CF had significantly higher moisture content compared to the growth promoters enriched feeds. [16] have reported similar lipid levels in carp grower feeds. The experimental feeds were formulated with similar dietary lipid levels with no significant difference that ranged from 5.25±0.13% (CG) to 5.42±0.15% (EG).…”
Section: Proximate Composition Of Feedsmentioning
confidence: 61%
“…The moisture content of CF was found to be 14.02±0.16% which somewhat exceeds the desirable limit. Nayeem et al [16] reported that several manufacturers in Bangladesh produce feeds with moisture content above 12% and exceeding 15% in some cases. However, the moisture content in the experimental feeds was kept under a reasonable limit during formulation ranging from 10.80±0.12% (AP) to 10.89±0.08% (EG).…”
Section: Proximate Composition Of Feedsmentioning
confidence: 99%